Industri Buzzer dan Polarisasi Politik di Era Digital: Perspektif Ekonomi Politik Media - Syadila, Ayu Valysha; Quinna, Masayu Syakira; Auliya, Shofwah Hilyatul; Aminulloh, Akhirul (Tuturlogi: Journal of Southeast Asian Communication, 2025)
Buzzers are employed as tools to sustain political power, wherein media owners and other political actors provide incentives to buzzers in the form of financial rewards or political appointments. This practice frequently violates provisions of the Electronic Information and Transactions Law (ITE Law) and has the potential to foster a hegemonic view that politics is inherently about provocation and mutual attacks. Although the ITE Law was originally designed to ensure safety and comfort in online communication, in practice—particularly within the context of the buzzer industry—it can be manipulated as an instrument to serve various vested interests. This study focuses on how media owners mobilize the masses into buzzers to influence multiple spheres of life, including politics, public policy, and social domains. The primary objective of this research is to understand and analyze the impact of buzzer practices on political polarization and social stability within society. A descriptive qualitative approach is employed, using literature review analysis to explore in depth the relationship between the buzzer industry and political polarization as a consequence of social media usage, from the perspective of the political economy of media. The findings indicate that buzzers intensify political polarization through agenda-setting strategies and the commodification of opinion. Within the political economy framework, the practice of political buzzers also contributes to the reproduction of power imbalances in the digital space.